AUF1 ligand circPCNX reduces cell proliferation by competing with p21 mRNA to increase p21 production. Issue 3 (14th January 2021) - Tsitsipatis, Dimitrios; Grammatikakis, Ioannis; Driscoll, Riley K; Yang, Xiaoling; Abdelmohsen, Kotb; Harris, Sophia C; Yang, Jen-Hao; Herman, Allison B; Chang, Ming-Wen; Munk, Rachel; Martindale, Jennifer L; Mazan-Mamczarz, Krystyna; et al.
Abstract: Mammalian circRNAs can influence different cellular processes by interacting with proteins and other nucleic acids. Here, we used ribonucleoprotein immunoprecipitation (RIP) analysis to identify systematically the circRNAs associated with the cancer-related protein AUF1. Among the circRNAs interacting with AUF1 in HeLa (human cervical carcinoma) cells, we focused on hsa_circ_0032434 ( circPCNX ), an abundant target of AUF1. Overexpression of circPCNX specifically interfered with the binding of AUF1 to p21 ( CDKN1A ) mRNA, thereby promoting p21 mRNA stability and elevating the production of p21, a major inhibitor of cell proliferation. Conversely, silencing circPCNX increased AUF1 binding to p21 mRNA, reducing p21 production and promoting cell division. Importantly, eliminating the AUF1-binding region of circPCNX abrogated the rise in p21 levels and rescued proliferation. Therefore, we propose that the interaction of circPCNX with AUF1 selectively prevents AUF1 binding to p21 mRNA, leading to enhanced p21 mRNA stability and p21 protein production, thereby suppressing cell growth.